Geologia da região de Presidente Olegário e evolução tectono-sedimentar do Grupo Areado, Eocretáceo da Bacia Sanfranciscana, Minas Gerais - Daniel Galvao Carnier Fragoso (2011)
In Presidente Olegario Sheet (SE.2E-Y-B-I), northwestern Minas Gerais state, occurs essentially sedimentary rocks related to Sao Francisco Basin. The oldest rocks, assigned to the Neoproterozoic, belongs to the Bambui Group, which are there composed by the following formations: Lagoa do Jacaré (calcarenite, calcisiltite, biolithite, dolomite, marl and siltstone), Serra da Saudade (siltstone and lenses ofcalcisiltites) and Tres Marias (feldspathic sandstone and siltstone), besides the newly designated Lagoa Formosa Formation (siltstone and diamictite). In general, these lithological associations represent a marine shelf sedimentation in a foreland basin. Unconformably covering the Bambui Group occur thick cretaceous deposits of the Areado and Mata da Corda groups. The Areado Group, more expressive unit of the region, is the main focus of this dissertation. Corresponds to the basal sedimentaryrecord of the Abaeté Subbasin, Sanfranciscana basin, that comprises the Abaete (conglomerate, breccia and sandstone), Quirico (siltstone, rhythmite and shale) and Tres Barras (stratified sandstone) formations, and represents a continental sedimentation related to the extensional tectonics occurred in South America during Early Cretaceous. For this unit, seven facies associatins were identified, mappable in 1:100.000 scale, that configure four Stratigraphic Intervals: 1 - Braided fluvial fans system associated with shallow lake deposits and locally eolian sedimentation; 2 - La.ke system with mainly pelagic and turbiditedeposition; 3 Fluvialdeltaic system; 4 Eolian system. The obtained structural data, in association with the regional Bouguer anomalies and the spatial distribution of the facies associations, suggest that the receiving basin has a "horst and graben" geometry, developedsimultaneously with the sedimentation. Palynological analysis of the Stratigraphic Interval 2, suggests a desoxicanoxic depositional environment, recording low energy sedimentation in deep water lakes. Two depositional sequences were defined through the stratigraphic analysis. The first, corresponding to tectonic-controlled sedimentation, is composed of three tectonic system tracts: Initial Rift Tectonic System Tract (Interval 1); Climax Rift Tectonic System Tract (Interval 2), Post-rift Tectonic System Tract (Interval 3). The second sequence consistsonly of the fourth interval and is characterized as a sedimentary expansion that exceeds the basin boundaries, which may be related to a postrift thermal subsidence. Finally, over the Areado Group occurs the effusive, pyroclastic and epiclastic rocks attributed to Mata da Corda Group, recording the volcanic activity that affected the region during Early Cretaceous.